Gender lens investing : - Quinlan, Joseph P. (John Wiley and Sons, 2017)
Delve into gender lens investing and the reality of the female economy Women today are an unparalleled force in the global economy-as successful entrepreneurs, corporate executives and family breadwinners. Yet gender-based violence, the absence of women's legal rights and the persistent wage gap stubbornly remain. This paradox creates an unprecedented and underexplored opportunity for investors. Gender Lens Investing, co-authored by Jackie VanderBrug, Managing Director and Joseph Quinlan, Managing Director and Chief Market Strategist, of U.S. Trust, Bank of America Private Wealth Management, is the first book of its kind to examine, in-depth the advantages of integrating gender into investment analysis. While other books speak to growing numbers and influence of women, Gender Lens Investing moves from economic trends to financial strategy. -Learn why gender is material to economic prosperity and investment performance -Explore ways to use a gender lens to assess products, companies and sectors. -Delve into the forces of positive social change supported by a gender perspective on investment choices -Examine profitable and gratifying gender lens investment strategies Women are one of the world's greatest underutilized assets, and applying a gender lens allows you to identify companies that recognize this, or uncover the risks of companies that neglect it. A gender lens adds value across the investment community, but the impact reaches far beyond the bounds of portfolios to the economy and society as a whole. Gender Lens Investing provides expert perspective and real-world practical insight for investors looking to drive returns and impact.